Systematic Review Keanekaragaman Spesies Leptospira pada Sampel Lingkungan di Asia - Yulia Sayanthi; Dewi Susanna (Jurnal Kesehatan Lingkungan, 2021)
Leptospira was classified into three groups, namely pathogenic, intermediate, and saprophytic. Pathogenic Leptospira caused human and animal Leptospirosis, Leptospira intermediate recently found in human but not reproduce disease, meanwhile Leptopsira from the saprophytic group is an environmental species and considered not to caused disease. This study aims to do a systematic review of the diversity of Leptospira species from environmental samples in Asia. Based on this review, Leptospira from all groups were identified from environmental samples in Asia. Dominant pathogenic Leptopsira is L. kmetyi, Leptospira intermediate is L. wolffii Anda the dominant Leptospira from saprophytic group is L. meyeri. For further Leptospira, a detection study is recommended to classify Leptospira base on four subclades, namely P1, P2, S1 and S2. Knowing the classification of Leptospira from environmental samples will be able to provide information about where and how the transmission of Leptospirosis occurs.